Соціальні інтереси крізь призму постмодерністської епістемології - Александров, Денис Валентинович; Aleksandrov, Denys (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті проаналізовано епістемологічне навантаження та виявлено особливості інтерпретації соціальних інтересів в умовах методологічного релятивізму, плюралізму підходів, партикулярності наукових поглядів. В основу покладено принцип історизму й компаративістський підхід до визначення асоціативності понять, що розкривають зміст феномену. Розглянуто спробу сучасних західних соціологів відокремити соціальні інтереси від детерміністичної інтерпретації, застосовувати їх у пробабілістському поясненні просторово-часових «контурів» соціальних практик. Акцентовано увагу на визнанні вченими спонтанної наповненості, непередбаченості та спорадичності соціальних інтересів як специфічного виду надіндивідуального зв’язку, що уможливлює перехід потенційного й бажаного буття в реальне. The article is devoted to the analyses the specific of elaboration of social interests in modern social theory. The author makes an attempt to define heuristic, methodological and logic functions of concept of social interest. The use of historical method, system method and conceptual analysis enabled to trace the evolution of scientific outlook of social interest as a phenomenon. The use of system approach provided the association of concepts, by which social interests were interpreted in modern and postmodern sociological theories. By means of conceptual analysis it was set the semantics of the social concept, methodological conditionality of its values. It is grounded the specific ability of interest to be an interlink of social relations, providing dialectical unity of agent and social reality. The author shows the attempts of modern sociologists to overcome insufficiency of sociological equation of interest to an economic value or psychological orientation of attention, offering strategy of explanation of social interest as a specific «intermediary» unit, which determines and directs social relations. Attention is also focused on the ability of concept of interest to expose the new verges of its maintenance and to get heuristic possibilities by means of methodological relativism, pluralism, temporality. Is examined the attempt of sociologists to dissociate the concept of interest from deterministic interpretation, to use it in the explanation of spatiotemporal «contours» of social practice. Is grounded unforeseen and openness of modern social processes in which social interest as a temporary phenomenon denotes a specific type of super individual connection and specifies on passing of potential and desired being to the real being.
Social Interests through the Prism of Postmodern Epistemology
Keywords: соціальний інтерес; епістемологія; сучасна західна соціологічна теорія; social interests; epistemology; modern and postmodern social theory